Global development and precarity: a critical political analysis. Issue 4 (7th June 2019) - Suliman, Samid; Weber, Heloise
ABSTRACT: Precarity as a concept has come to be conceived as a distinctive experience of neoliberal development, especially in the European context. The experience of precarity, according to some, has influenced efforts aimed at living otherwise from the precepts of neoliberal development. Yet, for others, precarity is producing a 'new dangerous class'. However, despite different perspectives of the effects and implications of precarity, the analytical purchase and political utility of the concept has received insufficient attention. In this article, we hope to contribute to critical debates on the limitations of 'precarity' as a concept for critical political analysis. We argue that in the dominant use of precarity as an analytic of inequality, particular experiences are rendered as historical universals. Consequently, these (particular) experiences are disconnected from global social and political relations of inequality, while at the same time reinforcing a linear and reductionist conception of development. We demonstrate that the temporal scheme represented by the notion of the 'age of post-Fordism', which serves as a crucial marker of the explanatory framework of precarity (in Europe), actually misconstrues the politics of global development through inequalities. Moreover, the tendency to focus on subjectification as conditioning the formation of a 'new' dangerous class, entails far-reaching omissions of actual transnational political struggles against domination and inequality. Instead of precarity, a critical engagement with the politics of global development ought to be the subject of analysis for understanding contested relations of affluence, insecurity and inequality.